The fall [videorecording (DVD)] - Singh, Tarsem; Pace, Lee, 1979-; Waddell, Justine; Untaru, Catinca, 1997-; Petrov, Valeri, 1920-2014 (Sony Pictures Home Entertainment, 2008)
1920's, Los Angeles. In a hospital on the outskirts of town, Roy Walker, an injured stuntman, begins to tell young Alexandria, a fellow patient with a broken arm, a fantastical story about 5 mythical heroes. Thanks to his fractured state of mind and her vivid imagination, the line between fiction and reality starts to blur as the tale advances.